Preface to philosophy - "Rickman, H.P." (London, 1964)
A PREFACE TO PHILOSOPHY prepares readers for the challenges of studying philosophy and writing philosophical essays. This classic textbook, in print for over thirty years, addresses such foundational topics as discerning philosophical questions, the purpose of philosophy, and the practice of doing philosophy. With its brief, accessible format and conversational writing style, A PREFACE TO PHILOSOPHY, is a perfect compliment to a traditional Introduction to Philosophy textbook.
Keywords: Philosophy